Analysis of Suspended Potential Discharge Defects by SF6 Decomposition Products. Issue 1 (October 2021) - Fu, Lijun; Guan, Yanling; Zhang, Liang; Zhang, Jian
Abstract: The type and content of SF6 decomposition products are directly related to the type, location and degree of fault. Based on the analysis of the abnormal SF6 gas decomposition product content and discharge type of 126kV Porcelain Column type circuit breaker, the potential fault of the circuit breaker is judged to be suspension potential discharge fault. After disassembling the circuit breaker, it is found that the abnormal phase of the insulation rod is deformed, the pin become thin, and there are solid decomposition products, the sulfides and fluoride, which are mainly composed of iron, aluminum, chromium and manganese, further confirm that the potential fault of the circuit breaker is suspension potential discharge fault. The forming process and reaction mechanism of the suspended potential discharge fault are analyzed. Once the fault occurs, its function will promote the development of the fault. The influence of the suspension potential discharge fault on the performance of the circuit breaker is also analyzed. When the suspension potential discharge fault exists, it will cause the abnormality and even affect the normal operation of the circuit breake.